Routledge international handbook of participatory design - Simonsen, Jesper; Robertson, Toni (Routledge, 2013)
"Participatory Design is about the direct involvement of people in the co-design of the technologies they use. Its central concern is how co llaborative design processes can be driven by the participation of the people affected by the technology designed. Embracing a diverse colle ction of principles and practices aimed at making technologies, tools, environments, businesses, and social institutions more responsive to human needs, the International Handbook of Participatory Design is a s tate-of-the-art reference handbook for the subject. The Handbook bring s together a multidisciplinary and international group of highly recog nized and experienced experts to present an authoritative overview of the field and its history and discuss contributions and challenges of the pivotal issues in Participatory Design, including heritage, ethics , ethnography, methods, tools and techniques and community involvement . The book also highlights three large-scale case studies which show h ow Participatory Design has been used to bring about outstanding chang es in different organisations. The book shows why Participatory Design is an important, highly relevant and rewarding area for research and practice. It will be an invaluable resource for students, researchers, scholars and professionals in Participatory Design"–